A predictive model for the time dependence of concentrations in plating baths. (5th August 2019) - Baumer, Christoph; Bund, Andreas; Herrmann, Johannes
Abstract: An industrial electroplating process is usually based on a long‐term and intensive use of the electrolytes. In most cases, ten to several hundred metal turnovers (MTO) are deposited from a commercial bath. As a consequence, the composition of the electrolyte can change drastically during its use. Furthermore, some bath components are difficult to determine and therefore are not analyzed routinely or not analyzed at all. In this paper is shown how the control of the electrolytes can be realized by mass balances and analyzing of the main components. For this purpose, a nonlinear model for the calculation of the concentration considering drag‐out and the reaction mechanism is defined. Based on this model, the composition of the electrolyte is simulated considering the replenishment and dilution of the bath. By using simulated annealing, the simulated concentrations are fitted to the real concentrations. Based on the known reaction system, the normally unknown characteristic parameters of the deposition like drag‐out, deposited mass, current efficiency, and alloy composition are obtained. These values can then be used for improving process control and calculations of regular additions of bath components. Additionally, this procedure describes a general systematic to validate hypothetical considerations of the reaction mechanism in a galvanic process by practical data. Abstract : Characteristic parameters of the plating process like drag‐out, deposited mass, current efficiency, and alloy composition are calculated by mass balances and analyzing of the main components using a nonlinear model which reflects the reality well. By knowing the characteristic parameters, future concentration changes can be simulated for the control of the electrolyte. The method is shown on the industrial process of electroless nickel deposition, and the results are verified by external measurements.